SOEs Legal Regime of After the 2025 Law: Status on State Finance and State Administration - Bagus Satrio Utomo (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
Indonesian State-Owned Enterprises (SOEs/BUMN) have historically operated within a legal framework containing a conflict between public and private law. This dualism exposes executives to criminalization risk for ordinary business losses. This study examines the cumulative 2025 legislative reforms, culminating in Law (UU) Number 16 of 2025 (The Fourth Amendment to the BUMN Law), to assess its effectiveness in resolving this legal dualism. The new law introduces a radical separation of regulator (BP BUMN) and operator (Danantara) functions. It legally redefines BUMN assets as corporate property (Article 4A(5)) and stipulates that an BUMN's loss is not a "state loss" (Article 4B). The findings show that Law No. 16 of 2025 provides a definitive normative solution to the ambiguity over BUMN assets and establishes a robust legislative foundation for the Business Judgment Rule (BJR). However, this reform introduces a new, sharp antinomy (disharmony of norms) by retaining the full audit authority of the Supreme Audit Agency (BPK) under Article 71(2). This provision directly conflicts with the new private-corporate status of BUMNs. The primary recommendations are the urgent legislative harmonization of the BPK Law, the Anti-Corruption Law, and the KPK Law to align the public accountability framework with this new corporate paradigm.